Creative destruction and fiscal institutions: A long-run case study of three regions - Jan Schnellenbach; Thushyanthan Baskaran; Lars P. Feld (Max Planck Institute of Economics, 2009)
We analyze the rise and decline of the steel and mining industries in the regions of Saarland, Lorraine und Luxemburg over a long period, from the mid-19th century to 2003. Our main focus in on the period of structural decline in these industries after the second world war. Differences in the institutional framework of these regions are exploited to analyze how the broader fiscal constitution sets incentives for governments to either obstruct or to encourage structural change in the private sector. Our main result is that fiscal autonomy of a region subjected to structural change in its private sector is associated with a relatively faster decline of employment in the sectors affected. Contrary to the political lore, fiscal transfers are not used to speed up the destruction of old sectors, but rather to stabilize incomes.
Keywords: E63; E64; H77; H54; 330; structural change; scal federalism; grants in aid; creative destruction